VONIS SANKSI PIDANA TAMBAHAN OLEH HAKIM BERUPA PENGEMBALIAN KERUGIAN KEUANGAN NEGARA OLEH TERPIDANA TINDAK PIDANA KORUPSI DI PENGADILAN NEGERI DENPASAR - Setiabudhi, I Ketut Rai (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2014)
Corruption in Indonesia has been so severed and widespread in the community and very alarming, its development continues to increase from year to year, both in number of cases and the amount of state financial losses and in terms of quality. These criminal offenses commit more systematic and scope into all aspects of life, Starting from lower level of the dominant and state officials or law enforcement. Judge in imposing sanctions not only imprisonment and also fined an additional punishment, including the return of financial loss to the state by state corruption, as well as some Denpasar District Court and the Court of Criminal Acts of Corruption  (TIPIKOR) Denpasar. Legal basis of corruption in the judicial process is used by judges Act NO: 31 Jo Act 1999 NO: 20 of 2001 on Eradication of Corruption.
Keywords: additional punishment; corruption; financial losses